Perkawinan Beda Agama dalam Perspektif Hukum Nasional: Antara Legalitas dan Realitas Sosial - Erleni; Mujiburrahman (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2023)
Interfaith marriage in Indonesia continues to spark legal debate because Law No. 1 of 1974 only recognizes marriages as valid if they comply with the religious laws of each party, without explicitly regulating interfaith marriages. This situation creates a legal vacuum, so that couples of different faiths often seek alternatives to legalize their marriages. This normative study shows that the validity of marriage remains dependent on the religious rules of each party, while civil recognition may refer to provisions in the Population Administration Law. Therefore, regulatory clarity is needed to ensure legal certainty and protect the rights of citizens.